THE THEME OF LOVE AND DEATH IN EMILY DICKINSON’S POETRY - Radhakrishna G V (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Emily Dickinson’s poetry intricately explores the themes of love and death, two fundamental aspects of human existence. Her portrayal of love goes beyond traditional romantic notions, encompassing deep longing, spiritual connection, and the pain of separation. Love in Dickinson’s poetry often transcends mortality, persisting beyond physical existence and appearing as both a source of joy and suffering. At the same time, death is a recurring theme in her work, depicted not as a fearsome end but as a natural transition, sometimes personified as a gentle guide or an inevitable companion. Rather than presenting death with dread, Dickinson approaches it with curiosity, ambiguity, and, at times, a sense of peace. What makes Dickinson’s treatment of love and death unique is the way she intertwines them, suggesting that love can survive death and that death itself can be an expression of love. Her poetry reflects a deep engagement with existential questions, often leaving room for multiple interpretations. The use of unconventional syntax, dashes, and capitalization enhances the complexity of her themes, reinforcing the sense of mystery and intensity in her reflections on love and mortality. This paper examines Dickinson’s exploration of love and death through her poetic imagery, philosophical depth, and stylistic innovations. By analyzing her works, it becomes clear that love and death are not opposites in her poetry but rather two forces that define and shape human experience. Dickinson’s ability to merge these themes with emotional depth and literary brilliance ensures her lasting influence in American literature.